economics of abortion and children in care - Bagaria, Manish (2007)
This paper investigates the relationship between abortion and children in care. Data from 1967 to 1973 are used to test the hypothesis, whether or not legalisation of abortion in England had some effect on the number children in care. The motivation of this research comes from the negative association between abortion rates and reported crime found by Donohue and Levitt (2001) for the U.S. and replication of the same in the U.K in Kahane's, Paton's and Simmons research (2007). Although children in care may be an important link in the chain connecting abortion to other social outcomes such as crime, to date no studies have tested whether legalising abortion has a direct impact on the number of children in care. It is this gap the literature that I intend to address in this dissertation. Using data from local authorities in England, I found some evidence of a positive relationship between changes in the number of abortions and the number of children in care.